Evaluation of the effectiveness of dequalinium chloride vaginal tablets in aerobic vaginitis: A placebo-controlled study - Tekgunduz, Sibel Ejder; Saracoglu, Ferit (Eastern Journal of Medical Sciences, 2021)
Background: Aerobic vaginitis is a disturbance of vaginal homeostasis caused by the colonization of enteric bacteria. They are not clinically well-defined and do not have standard treatment regimes. Hence, the present study was conducted to evaluate the effectiveness of dequalinium chloride topical vaginal administration in aerobic vaginitis in a placebo-controlled manner. Materials and Methods: This study was conducted in a placebo-controlled manner to demonstrate the effectiveness of vaginal 10 mg dequalinium chloride. A total of 30 patients with different vaginal infections were included in the study. The patients included in the study were divided between the drug group and the placebo group and were treated with one vaginal tablet daily for 6 days. The total symptom score, which consists of the assessment of discharge, itching, and burning sensation, and the lactobacillus grade evaluated microscopically, was determined. Results: It was found that the effectiveness of dequalinium chloride was very high compared to placebo (92% vs. 0%). The reproduction frequency in the first visit was statistically significantly lower in the drug group compared to the placebo group (P < 0.001). Conclusion: It was found that dequalinium chloride is effective for the treatment of aerobic vaginitis. However, studies containing a larger sample group, including the long-term effects (efficacy and side effects) of the drug, should be conducted to prove our conclusion.